Back to Nothing: Prisoner Reentry and Neoliberal Neglect - De Giorgi, Alessandro (Social justice, 2017)
The article discusses the social conditions of prisoners as they reenter society in Oakland, California within the context of U.S. neoliberalism, including in regard African American ex-convicts' experiences in Oakland. An overview of the minimal social services offered to ex-convicts in Oakland, including a community health clinic and the inability for ex-prisoners to attain subsidized housing, is provided.